Dynamic breakdown of passive films on stainless steel during in situ thermal oxidation. (December 2022) - Chen, Yanhui; Tang, Pengfei; Qiao, Shihang; Liu, Shanshan; Yang, Xiaomeng; Li, Ang
Abstract: The outstanding corrosion resistance of stainless-steel is from its passive oxide. Environmental transmission electron microscope was used in a modern atomic-scale in situ initial oxidation analysis process to reveal the microstructural and elemental variation on its breakdown. An amorphous oxide layer was the main oxide when temperatures is lower than 500 °C, and pits formed from 500 °C, and a porous structure formed from 700 °C. The protective passive films on the oxide/alloy interface were damaged by priority structural oxidation and prompted further alloy failure. The study provides direct experimental data beyond that of traditional research. Graphical Abstract: ga1 Highlights: Breakdown of the passive films of stainless steel requires a combination of complex reactions and its mechanism is still debatable. A modern in situ initial oxidation analysis process down to atomic scale in an environmental TEM was introduced to traditional metal corrosion on stainless steel. The protective passive films on the oxide/alloy interface were damaged by priority structural oxidation and prompted further alloy failure.